Pengaruh Skandal Politik Terhadap Kepercayaan Publik dan Kinerja Pemerintah di Indonesia - Aditama Putra Maulana (PSHPM Untag Semarang, 2025)
Government ethics encompass issues of honesty and transparency in governance. Government ethics must be upheld by elite public officials and government staff. Constitutional Court Decision Number 90/PUU-XXI/2023. This decision has sparked controversy and conflict in Indonesia because it is considered to involve political interests. The public questions the family ties between Constitutional Court Chief Justice Anwar Usman, who is President Jokowi's brother-in-law or Gibran's uncle. Based on the background of conflict and alleged political interests related to the Constitutional Court's ruling on the age limit for vice presidents, the relevant problem formulation is: what is the impact of the political scandal of Constitutional Court Decision No. 90/PUU-XXI/2023? Qualitative research focuses on gaining an in-depth understanding of social phenomena through document analysis to gather information. The research results reveal that the constitution can be manipulated by politics and the judiciary can be pressured to facilitate political interests.